Immunotherapy of Autoimmune Diseases with Nonantibiotic Properties of Tetracyclines - Park, Chan-Su (Immune Netw, 2020)
Tetracyclines, which have long been used as broad-spectrum antibiotics, also exhibit a variety of nonantibiotic activities including anti-inflammatory and immunomodulatory properties. Tetracyclines bind to the 30S ribosome of the bacteria and inhibit protein synthesis. Unlike antimicrobial activity, the primary molecular target for the nonantibiotic activity of tetracycline remains to be clarified. Nonetheless, the therapeutic efficacies of tetracyclines, particularly minocycline and doxycycline, have been demonstrated in various animal models of autoimmune disorders, such as multiple sclerosis, rheumatoid arthritis, and asthma. In this study, we summarized the anti-inflammatory and immunomodulatory activities of tetracyclines, focusing on the mechanisms underlying these activities. In addition, we highlighted the on-going or completed clinical trials with reported outcomes.